Transcatheter closure of a huge iatrogenic atrial septal defect: A case report. Issue 50 (December 2017) - Yang, Yong; Li, Xi; Chen, Mao; Feng, Yuan
Abstract: Rationale: Iatrogenic atrial septal defects caused by cardiac surgery are rare complications that are traditionally repaired through reoperations; unfortunately, reoperations are accompanied by high risk and trauma. Patient concerns: Herein, we report a rare case of a huge atrial septal defect after mitral and aortic mechanical valve replacement. Diagnoses: Transesophageal echocardiography revealed a 20 × 33 mm atrial septal defect with a mainly left-to-right shunt and bidirectional shunt. Interventions: The defect was successfully occluded using a Shape Memory septal occlude with a waist diameter of 42 mm. Outcomes: At follow-up 6 months after, the patient's symptoms were remarkably relieved and chest radiograph showed obvious improvement of the pulmonary congestion. Lessons: Percutaneous device treatment can be used as an alternative to surgery in iatrogenic atrial septal defects if the anatomical condition of the septal defect is appropriate for transcatheter closure.